Berlin International : Literaturszenen in der geteilten Stadt (1970‒1989) - Müller-Tamm, Jutta 1963- HerausgeberIn; Klengel, Susanne 1960- HerausgeberIn; Regeler, Lukas Nils 1993- HerausgeberIn; Schneider, Ulrike HerausgeberIn (De Gruyter, 2023)
By the time West Berlin was declared the European Capital of Culture of 1988, a heavily internationalized literary scene had already been developing on both sides of the Wall. In fifteen contributions, this volume traces the literary journey taken by the front, island, and capital city to become a future metropolis by looking at numerous case studies, focusing on authors who lived or were guests in Berlin in the 1970s and 1980s